Religious and spiritual coping of jewish bereavement - Yoffe, Laura (2017)
This article analyses religious and spiritual coping of negative and stressful events such as the loss of a loved one. The study cases of a religious jewish man and a woman- who lost a loved one- is part of my Docthoral Thesis (an exploratory and descriptive study done with religious persons of different creeds), where it was verified that participation in funerary jewish rituals, prayers, meditation, healing, and religious support promote positive effects and physical, psychological, mental and spiritual well- being of religious people who mourn the loss of a loved one